2017
DOI: 10.1038/s41559-017-0403-4
|View full text |Cite
|
Sign up to set email alerts
|

Pan-arthropod analysis reveals somatic piRNAs as an ancestral defence against transposable elements

Abstract: Summary Paragraph In animals, small RNA molecules termed PIWI-interacting RNAs (piRNAs) silence transposable elements (TEs), protecting the germline from genomic instability and mutation. piRNAs have been detected in the soma in a few animals, but these are believed to be specific adaptations of individual species. Here, we report that somatic piRNAs were likely present in the ancestral arthropod more than 500 million years ago. Analysis of 20 species across the arthropod phylum suggests that somatic piRNAs ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
253
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(280 citation statements)
references
References 53 publications
15
253
0
Order By: Relevance
“…concluded that these dust mite RdRps are processive enzymes (RRF3 type) that catalyze a series of consecutive reactions that release the template and lead to the synthesis of longer RNAs . In addition, the presence of RdRp in chelicerates suggests that arthropods originally used a plant‐like RNAi mechanism to silence transposable elements, indicating that small RNA silencing pathways have been repurposed for both somatic and germline functions throughout arthropod evolution . Thus, without further experimental studies, it is very difficult to claim that these five RdRp genes in T. urticae are involved in possible siRNA or RNAi amplification systems.…”
Section: Possible Factors That Enhance Systemic Movement Of Rna In MImentioning
confidence: 99%
See 1 more Smart Citation
“…concluded that these dust mite RdRps are processive enzymes (RRF3 type) that catalyze a series of consecutive reactions that release the template and lead to the synthesis of longer RNAs . In addition, the presence of RdRp in chelicerates suggests that arthropods originally used a plant‐like RNAi mechanism to silence transposable elements, indicating that small RNA silencing pathways have been repurposed for both somatic and germline functions throughout arthropod evolution . Thus, without further experimental studies, it is very difficult to claim that these five RdRp genes in T. urticae are involved in possible siRNA or RNAi amplification systems.…”
Section: Possible Factors That Enhance Systemic Movement Of Rna In MImentioning
confidence: 99%
“…Both miRNAs and siRNAs are post‐transcriptional regulators of RNA, while siRNAs can also be derived from viruses, and can thus be involved in key antiviral mechanisms . PiRNAs are longer than miRNAs and siRNAs, being 24–31 nt in length, and are highly abundant in germ cells . In the context of arthropod pest control and as a tool for the study of gene function, RNAi usually refers to the siRNA pathway .…”
Section: Introductionmentioning
confidence: 99%
“…In nematodes and arthropods, antiviral RNA-interference (RNAi) processes viral genomes into distinctive small RNAs (viRNAs) (Félix et al 2011;Lewis et al 2018). These can be sequenced from the metagenomic discovery RNA pool, and the reads mapped to RNAseq assemblies (their small size and patchy distribution mean that viRNA assemblies are fragmentary) (Aguiar et al 2015;Webster et al 2015).…”
Section: Going Beyond 'Virus-like Sequences'mentioning
confidence: 99%
“…Importantly, viRNAs usually have a tight and characteristic length distribution (e.g. 20nt in Lepidoptera, 21nt in Drosophila, 22nt in C. elegans) (Félix et al 2011;Lewis et al 2018) and a 3' 2-O-methyl group, making them distinguishable from degradation products. Their size distribution and base composition also distinguish them from TE-and EVE-derived piwi-associated RNAs (Palatini et al 2017;Lewis et al 2018;Waldron et al 2018).…”
Section: Going Beyond 'Virus-like Sequences'mentioning
confidence: 99%
“…The repetitive sequences of the introns also represent the preferred target sites of genetic parasites to invade the host genome, whereas the nonrepetitive sequences that code for proteins normally are not damaged or deformed by genome invading agents . Intriguingly, intronic regions that do not code for proteins in many cases serve as a rich source of RNAs that are used for defense against transposable elements, indicating additional roles in self/nonself‐discrimination …”
Section: Protein‐based Cellsmentioning
confidence: 99%